Celebrating Thirty Years of Theory Publishing in Amr: Award-Winning Articles from the First Two Decades Revisited - Kilduff, Martín (Academy of Management Review, 2007)
The article discusses the “Academy of Management Review“ (AMR) upon its 30-year anniversary in 2005. In that year, the editor asked a committee headed by Madan Pillutla and including Gerald F. Davis and Christopher P. Earley to pick what they considered to be the most innovative, frame-breaking article from each of the first two decades of published work in AMR. The seven choices made by the committee are reported. The article also discusses the founding of AMR during the 1973-1974 term when the Academy Board of Governors made the decision to establish a new journal devoted to theoretical and conceptual work. The focus was on “distinguished original manuscripts“ that moved “theoretical conceptualization forward“ with “clear implications of theory for problem solving.“